2016
DOI: 10.1007/s40732-016-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

The IRAP Is Nonrelative but not Acontextual: Changes to the Contrast Category Influence Men’s Dehumanization of Women

Abstract: The Implicit Relational Assessment Procedure (IRAP) is frequently employed over other measures of so-called implicit attitudes because it produces four independent and "non-relative" bias scores, thereby providing greater clarity around what drives an effect. Indeed, studies have sometimes emphasized the procedural separation of the four trial-types by choosing to report only the results of a single, theoretically meaningful trial-type. However, no research to date has examined the degree to which performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…By employing semantically complex stimuli and appealing to responses on a single trial-type, the results of the current study rely on the "non-relative" nature of the IRAP's four trial-types. While the task's four trial-types are indeed procedurally separated (e.g., "life-positive" trials did not contain stimuli related to either "death" or "negative"), it is worth noting that research that we have conducted elsewhere has demonstrated that responding on one IRAP trial-type is influenced by the contents of the others (Hussey, Ní Mhaoileoin, et al, 2015). For example, that responses on the "my death-negative" trial-type may have differed if this had been contrast with a category other than "my life".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing semantically complex stimuli and appealing to responses on a single trial-type, the results of the current study rely on the "non-relative" nature of the IRAP's four trial-types. While the task's four trial-types are indeed procedurally separated (e.g., "life-positive" trials did not contain stimuli related to either "death" or "negative"), it is worth noting that research that we have conducted elsewhere has demonstrated that responding on one IRAP trial-type is influenced by the contents of the others (Hussey, Ní Mhaoileoin, et al, 2015). For example, that responses on the "my death-negative" trial-type may have differed if this had been contrast with a category other than "my life".…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, each trial on the IRAP presents a specific category pairing in isolation (e.g., a "death-negative" trial contains no stimuli related to either "life" or "positive"). In doing so, the IRAP produces four separate and "non-relative" bias scores (Hussey, Thompson, McEnteggart, Barnes-Holmes, & Barnes-Holmes, 2015; although see Hussey, Ní Mhaoileoin, et al, 2015). In the context of the current study, this allows for the separation of evaluations of life as positive, life as negative, death as positive and death as negative.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one might compare evaluations of death on the IRAP between normative individuals and those with a history of suicidal behavior (e.g., ideation and/or attempts). Second, future research might seek to better understand the behavioral processes involved in IRAP performances themselves (e.g., Hussey, Ní Mhaoileoin, et al, 2015). In so doing, we would be in a better position to explain how unexpected or counterintuitive patterns of bias emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The response latency differential between stereotype-consistent and -inconsistent blocks is used to infer a person's implicit bias towards the stimuli influenced by historical and current contextual variables (Barnes-Holmes et al 2010). The IRAP is non-relative insofar as the fact that each of its four trialtype scores are calculated independently from the other trial-types (see Hughes et al 2017; see Hussey et al 2016). That is, for the trial-type relating men with STEM subjects, participants' response times are compared when they responded with 'True' versus 'False' only and are not compared with their responses to 'Men more suited to' Arts subjects.…”
Section: Implicit Relational Assessment Proceduresmentioning
confidence: 99%
“…We must also consider the possibility that the IRAP's sensitivity to extraneous variables (e.g., choice of contrasting label statement; Hussey et al 2016) limits the validity of comparisons across conditions and contexts. This is a potential issue of all measures of implicit bias which are likely susceptible to some degree of influence by contextual factors (Hussey et al 2016). It has been suggested that the IRAP's sensitivity may make replications across contexts complex (Golijani-Moghaddam et al 2013).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%